(untitled) (The Batuk, 2024)
Over the past decades, the Nepalese telecommunications sector has grown remarkable due to increasing use of smartphones in various purposes. Quality in cellular phone service is always assumed as primary factor to attract and retain customer, thus customer satisfaction in relation to this industry is vital for the companies. The users of cellular phone expect quality on various service provided and wish fair value and satisfaction. The purpose of the paper is to assess customer perception in five dimensions of service quality (i.e.; tangibility, reliability, responsiveness, assurance, and empathy) using SERVPERF model and their association with customer satisfaction. A structured questionnaire survey conducted to collect opinions from 336 sample representing service users of various service providers. The collected data was processed and analyzed using SPSS software. The questionnaire including 22 service quality measures and four satisfaction measures was used. The results from descriptive analysis suggested the presence of acceptable service quality. In addition, the Pearson’s correlation indicated positive and significant associations between the five dimensions of service quality and customer satisfaction.